Applying IFRS for accounting of cryptocurrencies - Liudmila LAPIȚKAIA; Alexandru LEAHOVCENCO (Eastern European Journal of Regional Studies)
This article addresses issues related to recognition, evaluation and reflection in accounting cryptocurrency in accordance with IFRS. Should be noted, that there is currently no specific IFRS standard that would disclose these issues. The article also discusses the debatable issues of recognition in the accounting of crypto-currencies. However, this article discusses the possibility of recognizing cryptocurrency as an asset and the way of application of IFRS for evaluation and recording of the cryptocurrencies. In this situation, it becomes necessary at the regulatory level to consolidate the rules for accounting for cryptocurrencies. This can be done in various ways, for example: to introduce additions to a number of International financial reporting standards, or to elaborate a separate IFRS that would disclose the features of accounting for cryptocurrencies.